THE FIRST EXPERIENCE IN THE EMBOLIZATION OF PROSTATIC ARTERIES IN PATIENTS WITH BENIGN PROSTATIC HYPERPLASIA - V. N. Pavlov; S. A. Kapranov; R. I. Safiullin; V. V. Plechev; O. V. Galimov; V. Sh. Ishmetov; A. O. Papoyan; T. R. Ibragimov; S. I. Blagodarov; K. I. Zavialov (Креативная хирургия и онкология, 2018)
Introduction. Our first experience in embolization of prostatic arteries at patients with benign prostatic hyperplasia had comprised patients with the symptoms of chronic urinary retention.Material and methods. The average age of patients (n=3) was 61.0±4 years. Among medical indications to embolization there were dysuria significantly degrading the patients’ life quality and their unwillingness to proceed to transurethral resection. Before the embolization of the prostatic artery, it is necessary to identify the place of its departure and its anastomosis by computed tomography. Successful operation was effectuated without microcatheter guides in 3 cases and with the application of microcatheter guides in 3 cases. For the purposes of embolization there were used spherical embolus HydroPearl sized 400 nm. No complications were reported neither in the operational nor in the post-operational periods.Results. All patients admitted a decrease in dysuria as well as the improvement in life quality already in 7–15 days after the endovascular invasion. Control ultrasound dopplerography was performed 3 months after intervention. Two patients with embolization showed decrease of prostate volume by 26%, and one patient — by 35%.Conclusions. Embolization of the prostatic arteries is a promising low-traumatic and safe method for treating patients with benign prostatic hyperplasia. It is necessary to further study its long-term results, to develop an optimized methodology — fast, simple and cheap, but not at the expense of efficiency and safety.